Traumatic stress within disaster-exposed occupations: overview of the literature and suggestions for the management of traumatic stress in the workplace. Issue 1 (13th December 2018) - Brooks, Samantha K; Rubin, G James; Greenberg, Neil
Abstract: Background: Many people who experience a disaster will do so as part of an occupational group, either by chance or due to the nature of their role. Sources of data: This review is based on literature published in scientific journals. Areas of agreement: There are many social and occupational factors, which affect post-disaster mental health. In particular, effective social support—both during and post-disaster—appears to enhance psychological resilience. Areas of controversy: There is conflicting evidence regarding the best way to support trauma-exposed employees. Many organisations carry out post-incident debriefing despite evidence that this is unhelpful. Growing points: Employees who are well supported tend to have better psychological outcomes and as a result may be more likely to perform well at work. Areas timely for developing research: The development and evaluation of workplace interventions designed to help managers facilitate psychological resilience in their workforce is a priority. Successful interventions could substantially increase resilience and reduce the risk of long-term mental health problems in trauma-exposed employees.